2018
DOI: 10.1158/1078-0432.ccr-17-2852
|View full text |Cite
|
Sign up to set email alerts
|

B7-H3 Negatively Modulates CTL-Mediated Cancer Immunity

Abstract: Anti-programmed-death-1 (PD-1) immunotherapy improves survival in non-small cell lung cancer (NSCLC), but some cases are refractory to treatment, thereby requiring alternative strategies. B7-H3, an immune-checkpoint molecule, is expressed in various malignancies. To our knowledge, this study is the first to evaluate B7-H3 expression in NSCLCs treated with anti-PD-1 therapy and the therapeutic potential of a combination of anti-PD-1 therapy and B7-H3 targeting. B7-H3 expression was evaluated immunohistochemical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 51 publications
(68 reference statements)
3
105
0
Order By: Relevance
“…B7-H3 was found to be overexpressed among several kinds of human cancer cells and was correlated with disease deteriorations [13][14][15][16][17][18][19] (Table 2). B7-H3 was recognized as a co-stimulatory molecule for immune reactions such as T cell activation and IFN-γ production [20].…”
Section: Biological Function Of B7-h3mentioning
confidence: 99%
“…B7-H3 was found to be overexpressed among several kinds of human cancer cells and was correlated with disease deteriorations [13][14][15][16][17][18][19] (Table 2). B7-H3 was recognized as a co-stimulatory molecule for immune reactions such as T cell activation and IFN-γ production [20].…”
Section: Biological Function Of B7-h3mentioning
confidence: 99%
“…A recent report shows that blockade of B7-H3 decreases tumor size and increases the number of CD8 + tumor infiltrating lymphocytes in syngeneic models of pancreatic cancer and lung cancer. 43 Another report indicates that antibody-mediated inhibition of B7-H3 reduces tumor growth as well as the number of tumor associated macrophages and myeloid derived suppressor cells in genetic 44 The utility of B7-H3 as a therapeutic target is further supported by a recent report using xenograft and allograft models of various carcinomas to demonstrate the efficacy of B7-H3 antibody-drug conjugates (ADCs) to successfully target both tumor cells and tumor associated vasculature, prolong survival, and reduce metastasis. 35 As it pertains to osteosarcoma, our data showing that increased B7-H3 expression correlates with poor survival is consistent with that of Wang et al, collectively indicating that this molecule may be an attractive immunotherapeutic target in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…B7-H3 is expressed in 70% to 80% of NSCLC cases. [ 32 , 33 ] High expression of this protein is correlated with smoking history and a shortened overall survival in patients. [ 32 ] Soluble B7-H3 in malignant pleural effusions is a potential biomarker for its correlation with the stage of NSCLC.…”
Section: Co-inhibitory T Lymphocyte Checkpointsmentioning
confidence: 99%
“…[ 34 ] In addition, B7-H3 is associated with refractoriness to PD-1 antibodies and effective anti-tumor activity by increasing CD8+ T cell infiltration, which was shown in the dual blockade of B7-H3 and PD-1. [ 33 ] Another study also reported that inhibition of B7-H3 could enhance the sensitivity to cisplatin chemotherapy. [ 35 ] Higher B7-H3 expression on tumors in human immunodeficiency virus (HIV)-infected lung cancer patients as compared with uninfected patients may provide clues for the treatment of HIV-infected lung cancer patients.…”
Section: Co-inhibitory T Lymphocyte Checkpointsmentioning
confidence: 99%